2024
DOI: 10.31223/x5q02p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated multi-proxy source-to-sink analysis of the Lower Cretaceous of the Essaouira-Agadir Basin.

Abstract: This study investigates the Provenance of the Barremian-Aptian fluvial clastics exposed in the Essaouira-Agadir Basin which bears an important potential in terms of offshore feeding of reservoir sands. Thin section petrography and SEM, heavy minerals analysis, and detrital zircon dating were conducted and integrated with a large dataset of published low-temperature thermochronology studies to model the associated source-to-sink system. The homogeneity of fingerprints throughout the basin indicated a single pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…This complex uplift history, which began with inversion of Palaeozoic basin within the Carboniferous Variscan orogenic cycle, led to formation, filling, exhumation and erosion of sedimentary sinks across north‐west Gondwana, triggering recycling of significant volumes of sediment across the Gondwana shelf and subsequent homogenisation of the zircon record, a process recorded in other sediment proxies. When studied, sediment geochemistry, petrography and heavy mineral analysis indicate sedimentary reworking as a key process during both Palaeozoic and Mesozoic times (Figure 8) (Accotto et al, 2019; Gärtner et al, 2017; Ghienne et al, 2018; Roquette et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This complex uplift history, which began with inversion of Palaeozoic basin within the Carboniferous Variscan orogenic cycle, led to formation, filling, exhumation and erosion of sedimentary sinks across north‐west Gondwana, triggering recycling of significant volumes of sediment across the Gondwana shelf and subsequent homogenisation of the zircon record, a process recorded in other sediment proxies. When studied, sediment geochemistry, petrography and heavy mineral analysis indicate sedimentary reworking as a key process during both Palaeozoic and Mesozoic times (Figure 8) (Accotto et al, 2019; Gärtner et al, 2017; Ghienne et al, 2018; Roquette et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This should, based on basement geology, see a shift in provenance from Eburnean and Pan‐African grains, to Pan‐African and Variscan grains with accessory Eburnean grains. However, outside of Permian samples from the High Atlas of Morocco (Perez et al, 2019), no such shift is observed in the detrital zircon U–Pb geochronology record (Azdimousa et al, 2019; Domènech et al, 2018; Roquette et al, 2021).…”
Section: Geological Settingmentioning
confidence: 99%